CARBOHYDRATES CONSUMPTION, PHYSICAL ACTIVITY WITH BLOOD GLUCOSE LEVELS IN ELDERLY PEOPLE AT BERABAN VILLAGE TABANAN - Pande Putu Dian Pratiwi; I Wayan Ambartana; Ni Made Dewantari (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2019)
Diabetes mellitus is one of the degenerative diseases whose sufferers continue to increase every year. One characteristic of Diabetes Mellitus is an increase in blood glucose beyond normal. Several factors can affect the increase in blood glucose, such as : age, genetic, physical activity and consumption of carbohydrate. The purpose of this research is to find the relation between level consumption of carbohydrates and physical activity with blood glucose levels the elderly at Beraban Village, Tabanan. The kind of research is observational by cross-sectional design. The amounts of sample are 91 people. Data of carbohydrate consumption levels were collected by the 2 X 24-hour record method, data of physical activity were collected by through interviews using physical activity forms, data of blood glucose levels were collected by taking blood using the Easy Touch GCU tool. Data was processed by Spearman Rank Correlation statistical analysis. Result of this research indicates that 60,4% of sample having less carbohydrate consumption, 63,7% having very mild physical activity and 92,3% having normal blood glucose levels. There is no correlation between the level consumption of carbohydrate and blood glucose levels (p 0,05). There was no correlation between physical activity and blood glucose levels (p 0,05).Keywords: Consumption of Carbohydrates, Physical Activity, Blood Glucose.